Photodynamic inactivation of planktonic cultures of Streptococcus mutans using erythrosine irradiated by LED - Esper, Maria Ângela Lacerda Rangel; Barbosa, Junia Oliveira; Alvarenga, Janaína de Araújo; Junqueira, Juliana Campos; Rastelli, Alessandra nara de Souza; Gonçalves, Sérgio Eduardo de Paiva (Brazilian Dental Science, 2020)
Objective: The aim of this in vitro study was to evaluate the efficacy of photodynamic inactivation (PDI) with erythrosine (E), using a light-emitting diode (LED) on planktonic cultures of Streptococcus mutans. Material and Methods: A Streptococcus mutans strain (UA 159) was used to prepare the suspensions containing 107 cells/mL, which was tested under different experimental conditions: a) LED irradiation in the presence of erythrosine as a photosensitizer (E+L+); b) LED irradiation only (P-L+); c) treatment with erythrosine only (E+L-); and d) no LED irradiation or photosensitizer (P) treatment, which served as a control group (P-L-). After treatment, strains were seeded onto MSBS agar for determination of the number of colony-forming units (CFU/mL). Results: The results were submitted to analysis of variance and the Tukey test (p < 0.05). No reduction in the number of CFU/mL was observed in the treatment group with erythrosine (E+L+) when compared to the control (P-L-). Conclusion: PDI using erythrosine did not reduce the number of CFUs per millimeter within the parameters in this study.KEYWORDSErythrosine; Decay; Photodynamic inactivation; Light-emitting diode.